PREPARATION AND CATALYTIC ACTIVITY FOR ISOPROPYL BENZENE CRACKING OF Co, Mo AND Co/Mo-Al2O3-PILLARED MONTMORILLONITE CATALYSTS - Hasanudin Hasanudin; Karna Wijaya; Budi Santoso (Indonesian Journal of Chemistry, 2009)
It has been prepared Co, Mo and Co/Mo-Al2O3-pillared montmorillonite catalysts using montmorillonite clay  as raw material. The structure and porosity of the catalysts were determined using N2 adsorption-desorption and FT-IR spectroscopy analysis methods. Isopropyl benzene cracking using these catalysts were used to test the catalytic activity and performance of Co, Mo and Co/Mo-Al2O3-pillared montmorillonites.  Characterization results showed that pillarization resulted in the increase of the total pore volume and specific surface area of the clay. Meanwhile, transition metals (Co, Mo and Co/Mo) loaded on Al2O3-pillared monmorillonites could increase the catalytic activity of the catalysts for isopropyl benzene cracking significantly.